Extensão universitária na Universidade Federal de São Carlos: (des)encontros com a educação popular - Cunha, Ana Luiza Salgado (2018)
This research investigated educational processes that emerge from the relationship between subjects through the University Extension. The choice of the theme was due to the understanding that the dialogical relationship between subjects in the groups of University Extension can be configured as a formative process that seeks to overcome the inequalities and the discriminations of historically oppressed subjects, based on strategies of resistance , struggle and emancipation in approaches to Popular Education. The purpose of this research was to describe and understand experiences of University Extension groups in processes of knowledge construction and their ( dis ) encounters with Popular Education. The methodology used was based on a bibliographical review regarding the production of knowledge in thematic on University, University Extension and Popular Education that allowed us to build the theoretical basis of this thesis. Through a mapping of the University Extension profile at the Federal University of São Carlos, we were able to build an archeology of this University in 2016 and, from this mapping, to find coordinators and coordinators of extension projects with whom we dialogued in the form of an interview.The analysis of data was done by Content Analysis, leading us to organize the data into four broad categories: A -pertainment and involvement; B- University Extension as a concept under construction; C- social extensionist practice and the educational processes that emerge from it; and D- Popular Education: Extension as praxis of (a) people of transformation. The results pointed to the strength of the Brazilian public university as a social, formative and formative institution, giving clues to the strengthening of Popular Education through University Extension. Also, they pointed out that the University Extensionpraxis produce educational processes. The results also show the possibility of reconfiguring the university curricula in which University Extension can be orientated from the perspective of the experience as a social formative practice, d we stationed the University Extension as a medium-activity of the University, a teacher - training center for students, teachers, technicians and community people. Another point is the UFSCar's commitment to areas still known as alternatives, with a considerable opening of the institution to other proposals for building knowledge. Still, we find a complexity of definitions of University Extension, a result of the social-historical process, which gives it plural character and multiple functions. On the meeting of the University Extension with Popular Education, this study pointed to the second as an educational praxis that values knowledge of the people and their realities, implying a better reading of social, political and economic reality. All the notes corroborate with the thesis that the University Extension, in its encounters with Popular Education, produces educational processes for another possible, horizontal and dialogical world.